Rethinking the Book of Al-â€˜Aql al-Siyasi al-â€˜Arabi and Indonesian Political Phenomenon - Ali Akhbar Abaib Mas Rabbani Lubis (Jurnal Penelitian, 2020)
This article focuses on al-â€˜Aql al-Siyasi al-â€˜Arabiâ€™s work and its relevance. It also touches the political phenomenon in Indonesia during 2016-2019 concerning â€œâ€œNKRI Bersyariah (Sharia Republic of Indonesia Unitary State)â€ discourse supported by FPI and â€œkhilafahâ€ discourse supported by HTI. The research method employed was qualitative one involving library research viewed from Pierre Bourdieauâ€™s perspective on habitus, field and distinction, and helped with interactive model of data analysis encompassing data reduction, data display, and conclusion drawing/verifying. The result shows that al-Jabiri views qabilah, ghanimah and aqidah as the habituated keywords since pre-Islam times. The temperament was manifested into the fighting for realizing the ideologies (aqidah) of â€œNKRI bersyariahâ€ initiated by FPI qabilah, and â€œkhilafahâ€ (transnational) initiated by HTI qabilah. These ideologies basically are the capitalism movement trading Islam (ghanimah) to interest group. The incarnation of al-Jabiriâ€™s terminology can be relevant to Indonesian political phenomenon.